Metacognitive Digital Environment to Support Learning of Mathematics (2016)
This paper presents a study on the effect of incorporating an educational strategy based on a digital metacognitive environment of planning, monitoring and control to support learning in mathematics. The research was conducted with a group of freshmen, who interacted with the learning environment in order to improve their capacity for self-regulation and learning achievement. The pre-experimental study, using objective and subjective tests and recognition of skills, allowed the comparison of the effect of metacognitive strategy in learning achievement and ability of selfregulation. The results revealed a positive effect of metacognitive strategy in student learning. Regarding the ability of self-regulation, the effect was demonstrated in the assessment that students made about their real status of knowledge. These results indicated a decrease in self-efficacy and orientation to intrinsic goals, on aspect that likely drove the students to be aware about what they knew.